Enablers to Exercise Participation in Progressive Supranuclear Palsy: Health Professional Perspectives - Morris, Meg E.; Slade, Susan C.; Bruce, Christopher; McGinley, Jennifer L.; Bloem, Bastiaan R. (Frontiers in Neurology, 2021)
Background: People living with progressive supranuclear palsy (PSP) experience considerable difficulties with movement, walking, balance, and oculo-motor control. The role of exercises and physical activities in mitigating the motor and non-motor symptoms of PSP remains uncertain. Aims: To identify the perspectives and beliefs of health professionals about the benefits, enablers and barriers to participation in exercise and physical activity across the course of disease progression of PSP. Methods: Qualitative methods, within a phenomenological framework, were used to obtain health professional perspectives and recommendations. Nurses and allied health professionals participated in focus groups and in-depth interviews. Questions derived from a systematic review on exercise for PSP and expert opinions guided the interviews, which were audio-recorded, transcribed verbatim and de-identified. Two researchers independently conducted a thematic analysis. Results: Nineteen participants from different disciplines (nursing, physiotherapy, occupational therapy and speech pathology) participated. Four main themes emerged: (i) exercise and activities were thought to be valuable for living well with PSP; (ii) provision of information about the benefits of exercise and physical activities facilitates uptake; (iii) an interdisciplinary team can meet the multi-factorial and changing needs for exercise and activity across the time-course of PSP; and (iv) care partners can assist with the implementation of exercise physical activity. Conclusion: Health professionals advocate physical therapies for people living with PSP. The expectation is that even in this very challenging patient population, structured exercises and physical activities can help to optimise health and wellbeing, enabling people to continue to participate in social roles. The actual merits of such interventions must now be taken to the test in clinical trials.